Nueva escuela aplicación de metodologías en educación inicial - Luje Zumba, Erika Dayana (2020)
The general objective of this researching is to determine the incidence of the methodology application of the new school in Early Education in the teaching – learning process in children of 4 years in the Community Educational Center "El Sembrador" in Pastocalle parish, Pastocalle center, Latacunga canton during the period 2019-2020. For this purpose, the qualitative and quantitative approach was used with a descriptive case study. The purpose is to interpret the technical methodologies and strategies in the educational practice in the new school at the initial education level from the constructivist education approach. The results give a respective training to the teachers about the New School Application of Methodologies in Initial Education, since the teachers have all their will to continue learning and generating the knowledge about the children, but one of the disadvantages is the lack of resources. It is composed of the following direct beneficiaries (24 boys and 34 girls) and indirect beneficiaries (3 female teachers and 1 male authority) in the Community Education Center "El Sembrador". From the perspective of new school education, it has been possible to analyze that in other countries education has evolved in the learning of children in a dynamic, creative, and motivating way, allowing the child to have a constructive learning as they are in the countries of Mexico, Colombia, and Cuba. From the analysis it is suggested to use new didactic strategies such as human interaction: in the socio-affective area, language, motor and cognitive. At methodology level, it was chosen the descriptive case study, since it is focused on the observation of teaching-learning process in the social area through a detailed analysis that can be understood. From the point of view, it is understandable because it takes up the research through the applied instruments of the pedagogues Maria Montessori and Waldorf, which allowed to obtain information data and theory related to the research. For this purpose, the instrument was used as a survey technique and the questionnaire instrument with the participants. The survey and the documentary analysis. The analysis was carried out by means of codification, analysis and interpretation. As a result, it was found that there is no use of elements, methodologies or strategies in new school education; for this reason, it was verified that the teaching-learning process continues with the traditionalist model and that there is no tendency to change new paradigms in order to transmit new knowledge, which deserves a deep reflection on the practice of methodology and to apply it as a teacher to achieve a transformation of a new application of methodologies in early education.